2021
DOI: 10.3866/pku.whxb202101004
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene Materials: Definition, Classification, and Preparation Strategies

Abstract: Since its emergence in 2004, graphene has attracted enormous attention because of its unique and fantastic properties, which signals the birth of two-dimensional (2D) nanomaterials. The strictly atomic-layered 2D structure endows graphene with unconventional optical, electronic, magnetic, and mechanical properties. Owing to these extraordinary features, graphene has exhibited great potential in various fields, such as biology, medicine, chemistry, physics, and the environment. Notably, when graphene is used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 95 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Low-dimensional graphene nanostructures can be functionalized by chemical, physical, or combined methods to tune their properties and further satisfy the requirements of their various applications 106 . Aimed at the application of transistor devices and gas/ions separation membranes, large amounts of tuning strategies have been applied to functionalize the NPGs.…”
Section: Recent Progress In the On-surface Synthesis Of Npgmentioning
confidence: 99%
“…Low-dimensional graphene nanostructures can be functionalized by chemical, physical, or combined methods to tune their properties and further satisfy the requirements of their various applications 106 . Aimed at the application of transistor devices and gas/ions separation membranes, large amounts of tuning strategies have been applied to functionalize the NPGs.…”
Section: Recent Progress In the On-surface Synthesis Of Npgmentioning
confidence: 99%
“…Graphene oxide (GO) is a derivative material of graphene. It not only has a two-dimensional sheet structure and large surface area like the graphene but also contains a large number of oxygen-containing groups such as hydroxyl, carboxyl and epoxy [22], which can be effectively combine with matrix materials to improve the interface properties of composites. It is found that the functionalisation of GO surface can be realised by chemical reaction and intermolecular interaction between the oxygen-containing group and APTES [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…As the most fascinating 2D material, graphene has attracted enormous research interest in the fields of electrochemical catalysis 1,2 and sensing 3 due to its extraordinary physicochemical properties. 4 To further improve the electrochemical features of graphene and to fulfill the increasing demands of various applications, much effort has been dedicated to functionalizing graphene, 5,6 such as introducing oxygen-containing groups, [7][8][9] changing the defect level, [10][11][12] altering the morphology 13 and so on. Until now, different approaches such as chemical reagent oxidization, 14 plasma etching 15,16 and electrochemical activation 17,18 have been developed for graphene functionalization.…”
Section: Introductionmentioning
confidence: 99%